Supervisi Akademik untuk Meningkatkan Kompetensi Guru di SD Laboratorium UKSW - Suhandi Astuti (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2017)
Identification conducted by the principle of SD Laboratory UKSW showed that the teachers were still not competent in doing learning assessment administration well. To solve these problems, the principal conducted academic supervision. The essence of the academic supervision is to help teachers develop professional capabilities. This was also done by the principle of SD Laboratory UKSW in solving problems related to the administration assessment of learning where there were some teachers in SD Laboratory UKSW not yet competent in preparing the learning assessment administration well. Supervision technique conducted by discussion. The result of supervision performed by principle of SD Laboratory UKSW showed an increasement. At the initial conditions the average level of competence of learning assessment administration preparation was 63.5 (ideal score of 100). After given the action, the average of competence of learning assessment administration preparation was increased to 89.6. The data showed that the competence of learning assessment administration preparation has increased 26.2%.